(untitled) (Bangladesh Veterinarian, 2019)
Pathological investigation of genital diseases in Black Bengal goats (Capra hircus) was done using slaughterhouse materials. A total of 256 female genitalia were collected from slaughterhouses of Kishoreganj district of Bangladesh during October 2016 to December 2018. The gross pathological changes were recorded and tissues from the affected organs were collected for histopathology. A total of 56 (21.9%) female genitalia showed one or more of the 84 different pathological changes. The prevalence of reproductive diseases increased with age: the highest number of lesions (34) was recorded in animals aged 19-24 months. The uterus showed the highest number of pathological lesions (44) followed by ovary (31), fallopian tube (5), cervix (2) and vagina (2). Major pathological changes were luteal cyst (7.4%), endometritis (6.3%) and pyometra (7.0%). The Bangladesh Veterinarian (2019) 36(1 - 2): 8-19